The Durango South Project (University of Arizona Press, 2024)
The Anthropological Papers of the University of Arizona is a peer-reviewed monograph series sponsored by the School of Anthropology. Established in 1959, the series publishes archaeological and ethnographic papers that use contemporary method and theory to investigate problems of anthropological importance in the southwestern United States, Mexico, and related areas.